Bibliometric Review Analysis of Academic Outcomes of Flipped Classroom in Physics Education Before and During Covid-19 - Yana, Annisa Ulfa; Handayanto, Supriyono Koes; Taufiq, Ahmad (Universitas Muhammadiyah Makassar, 2023)
The pedagogical approach known as the flipped classroom has gained significant popularity in both higher education and high school settings in recent years. This article aims to provide a comprehensive explanation regarding the comparison of flipped classroom academic results in physics education before and during the Covid-19 pandemic. The method used here was bibliometric-based literacy analysis using Publish or Perish (PoP) software and the VOSviewer application, which is focused on the keyword